2021
DOI: 10.1103/physrevlett.127.156401
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Hierarchy in Acoustic Topological Insulators

Abstract: Dirac cones are essential features of the electronic band structure of materials like graphene and topological insulators (TIs). Lately, this avenue has found a growing interest in classical wave physics by using engineered artificial lattices. Here, we demonstrate an acoustic 3D honeycomb lattice that features a Dirac hierarchy comprising an eightfold bulk Dirac cone, a 2D fourfold surface state Dirac cone, and a 1D twofold hinge state Dirac cone. The lifting of the Dirac degeneracy in each hierarchy authoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Further breaking these hinge states with a bandgap may hierarchically bring a third‐order corner state. [ 87] …”
Section: Acoustic Family Of 2d Qhe 3d Tis and Tsmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further breaking these hinge states with a bandgap may hierarchically bring a third‐order corner state. [ 87] …”
Section: Acoustic Family Of 2d Qhe 3d Tis and Tsmsmentioning
confidence: 99%
“…Further breaking these hinge states with a bandgap may hierarchically bring a third-order corner state. [ 87] In real 3D solid-state materials, dislocations are unavoidable defects, such as edge and screw dislocations. Their Burgers vectors are always integer values, probably possessing some real-space topological character.…”
Section: Three-dimensional Acoustic Tismentioning
confidence: 99%
“…Acoustic systems have served as important and versatile experimental platforms for demonstrating the physics of HOTIs. In particular, various types of HOTIs with corner modes have been realized in acoustics [70][71][72][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: Acoustic Higher-order Topological Insulating Phasesmentioning
confidence: 99%
“…In order to reduce the system to four equations, we first eliminate r G in (15), afterwards τ G and Γ G in Eq. ( 16) and (17) and finally, t G in Eq.…”
Section: Data Availabilitymentioning
confidence: 99%
“…An attractive motivation compared to their electronic counterparts is their easy fabrication and tunability, which often reveal novel and unexpected effects to lead to entirely differing analogous connection to the original physical context. Chern insulators, valley-Hall phases and higher-order topological insulators are a few of many arenas that have been conquered with classical wave acoustics [7][8][9][10][11][12][13][14][15][16] . Among the latest efforts, several groups have already demonstrated that structured and twisted bilayer plates indeed host striking sonic, vibrating and photonic similarities compared to twisted bilayer graphene physics [17][18][19][20][21][22] .…”
mentioning
confidence: 99%